Validity and reliability of hand and electronic timing for 40-yd sprint in college football players - Mann, J. B.; Ivey, P. J.; Brechue, W. F.; Mayhew, J. L. (The Journal of Strength and Conditioning Research, 2015)
The 40-yd sprint is the premier event for evaluating sprint speed among football players at all competitive levels. Some questions remain concerning the validity of hand timing compared with electronic timing, as well as the lack of assessment and reliability of each method. The purpose of this study was to evaluate the validity of hand timing by experienced and novice timers compared with electronic timing and to establish the reliability and smallest worthwhile difference (SWD) of each method for the 40-yd sprint. National Collegiate Athletic Association (NCAA) Division I college football players (n = 81) ran two 40-yd sprint trials, with each being timed electronically (touch pad start and infrared beam stop) and with hand-held stopwatches by 2 experienced and 4 novice timers. There was no significant difference between trials timed electronically or by experienced and novice timers. Hand timing (experienced = 4.90 ± 0.34 seconds; novice = 4.86 ± 0.33 seconds) produced a significantly faster 40-yd sprint time than electronic timing (5.12 ± 0.35 seconds) by 0.22 ± 0.07 and 0.26 ± 0.08 seconds, respectively. Relative reliability was extremely high for all comparisons with intraclass correlation coefficient >0.987. The SWD was 0.12 seconds with electronic timing and 0.14 seconds with hand timing. In conclusion, hand timing produces faster sprint times than electronic timing in college football players, independent of timer experience. Repeated 40-yd sprint trials have high relative reliability regardless of timing method. A meaningful change in 40-yd sprint performance is dependent on timing method used.